Factors Associated With Visible Anogenital Warts Among HIV-Uninfected Peruvian Men Who Have Sex With Men and Transwomen. Issue 4 (April 2015) - Galea, Jerome T.; Kinsler, Janni J.; Galan, Daniel Berrio; Calvo, Gino; Sánchez, Hugo; Leon, Segundo R.; Klausner, Jeffrey D.; Brown, Brandon
<x xml:space="preserve">Abstract</x> Background Visible, anogenital warts may be associated with risk factors for HIV infection. This cross-sectional study examined the factors associated with visible anogenital warts among HIV-uninfected Peruvian men who have sex with men (MSM) and transwomen. Methods Six hundred HIV-uninfected MSM and transwomen were recruited from a community-based setting in metropolitan Lima, Peru, through outreach activities. Participants were tested for syphilis, completed a behavioral questionnaire, and were examined for visible anogenital warts. Logistic regression was used to assess the independent association between sample characteristics, HIV-related risk factors, and visible anogenital warts. Results A tertiary education versus a primary/secondary (adjusted odds ratio [AOR], 1.79; 95% confidence interval [CI], 1.07–2.99), a first experience of anal intercourse at age 20 years or older versus younger ages (AOR, 2.80; 95% CI, 1.45–5.38), and self-reporting of current sexually transmitted infection symptoms (AOR, 2.38; 95% CI, 1.61–3.52) were significant correlates of visible anogenital warts, whereas syphilis infection, transactional sex, receptive anal intercourse, and self-identifying as a transwoman were not. Conclusions Although not associated with key risk factors for HIV infection in Peruvian MSM and transwomen, the presence of visible anogenital warts should prompt clinicians to consider the possibility of unreported same-sex sexual behaviors and other risk sexually transmitted infection/HIV risk factors.